ChemInform Abstract: Divergent Amine‐Catalyzed [2 + 2] Annulation of Allenoates with Azodicarboxylates: Facile Synthesis of 1, 2‐Diazetidines. Issue 12 (March 2016) - Xu, Silong; Chen, Jingrong; Shang, Jian; Qing, Ziqi; Zhang, Junjie; Tang, Yuhai
Abstract: The title [2 + 2] annulation reaction proceeds with excellent regio‐ and stereoselectivity to produce the corresponding 2‐diazetidines in moderate yields.